Assessing the magnetic order dependent γ-surface of Cr-Co-Ni alloys. (30th July 2021) - Yang, Zhibiao; Lu, Song; Tian, Yanzhong; Gu, Zijian; Mao, Huahai; Sun, Jian; Vitos, Levente
Graphical abstract: Highlights: A comprehensive database of stacking fault energy in Cr-Co-Ni alloys is obtained. The general relations between stable and unstable stacking fault energies are discussed. Composition and magnetism dependent deformation mechanism is predicted. Predicted prevalent deformation mode agrees well with experimental observations. Our results facilitate designing new Cr-Co-Ni alloys with high strength and ductility. Abstract: In order to efficiently explore the nearly infinite composition space in multicomponent solid solution alloys for reaching higher mechanical performance, it is important to establish predictive design strategies using computation-aided methods. Here, using ab initio calculations we systematically study the effects of magnetism and chemical composition on the generalized stacking fault energy surface (γ-surface) of Cr-Co-Ni medium entropy alloys and show that both chemistry and the coupled magnetic state strongly affect the γ-surface, consequently, the primary deformation modes. The relations among various stable and unstable stacking fault energies are revealed and discussed. The present findings are useful for studying the deformation behaviors of Cr-Co-Ni alloys and facilitate a density functional theory based design of transformation-induced plasticity and twinning-induced plasticity mechanisms in Cr-Co-Ni alloys.